Human smuggling - Guido Friebel; Sergei Guriev (Institute for the Study of Labor (IZA), 2012)
Despite its importance in global illegal migration, there is little, and mostly theoretical research on human smuggling. We suggest an analytical framework to understand the micro structure of the human smuggling market. Migrants interact with smuggling and financing intermediaries; these may or may not be integrated with each other, and with the migrants' employers. Policies of receiving countries (border controls, employer sanctions, deportation policies, sales of visa) affect the interactions in the smuggling market, and, hence, migration flows. We review the theoretical work, point to the scarce empirical evidence, and identify challenges for future theoretical, empirical work and policy advice.
urn:nbn:de:101:1-201205026162
Keywords: J15; J61; 330; illegal migration; trafficking; Illegale Einwanderung; Menschenhandel; Theorie